Centralized medical practice management software system - Ali, Khaled Mohammad; Salehin, Mohammad Ashikus; Hassan, Tahmid; Khan, Omar Hassan (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.